PROPAGATION AND CALLUS REGENERATION OF POTATO (SOLANUM TUBEROSUM L.) CULTIVAR ‘DESIREE’ UNDER SALT STRESS CONDITIONS - Atheel N. Yousef; Gharbia H. Danial; Diaa A. Ibrahim; Sazan E. Barakat (Science Journal of University of Zakho, 2024)
Under laboratory conditions, segments of potato with single nodes were exposed to varying doses of Sodium Chloride (NaCl) (0 mM, 20 mM, 40 mM, 60 mM, 80 mM and 100 mM), using the Murashige and Skoog growth medium to assess how NaCl salt stress affects   micropropagation, callus formation, and regeneration in the ‘Desiree’ potato plant cultivar, and also seeks to determine the ability of this cultivar to thrive in salt stress conditions.  The data were collected after a six-week period for each salt treatment. Remarkably, a significant increase in the mass of green and dry stems and roots was observed specifically under the 40 mM NaCl treatment. Conversely, the length of shoots and branches experienced a reduction as the NaCl concentration increased. The overall impact of the NaCl treatments strongly influenced root weight. Concerning the formation (development) and revitalization of callus, segments of potato microtubers were exposed to the above-mentioned NaCl concentrations, resulting in an intermediate level of salt stress that significantly reduced callus weights as NaCl concentration increased. Furthermore, a gradual decrease in the regeneration rate was noted with increasing concentrations of the plant growth regulator BA (1 to 4 mg/l). The most profound relative regeneration rate occurred at 1 mg/l BA. Notably, the counteractive effect of salt was more apparent with higher NaCl concentrations, with exceptions at 20 mM and 40 mM. These findings propose that the ‘Desiree’ potato cultivar exhibits moderate tolerance to salt stress and indicates a capacity to endure salinity. Moreover, this valuable variety could potentially be harnessed through genetic manipulation to enhance its salt resilience.